1979
DOI: 10.1177/004728757901700402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Vacation Travel in Response to Motor Fuel Shortages and Higher Prices

Abstract: This study presents findings from a survey administered in November 1975 among a sample of households in southeastern Wisconsin to determine, among other things, the shifts in travel vacations that occurred in response to the higher fuel prices that developed between 1973 and 1975 and that might occur in response to the alternative futures of still higher fuel prices and restricted fuel availability. Specific socioeconomic variables significantly distinguished between households that changed vacation plans an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

1982
1982
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 0 publications
1
12
0
Order By: Relevance
“…The standard deviations -which indicate the dispersion -are all larger than 1. Interestingly, this finding is in accordance with the findings of studies conducted during or in the aftermath of the oil crises (Corsi and Harvey, 1979;Kamp et al, 1979;Williams et al, 1979). The relatively unpopular response of picking another mode of transport (Response 6) was to some extent to be expected since for many destinations -particularly intercontinental destinations -air travel is generally considered to be the only viable alternative (Hares et al, 2010).…”
Section: Data Collectionsupporting
confidence: 82%
See 4 more Smart Citations
“…The standard deviations -which indicate the dispersion -are all larger than 1. Interestingly, this finding is in accordance with the findings of studies conducted during or in the aftermath of the oil crises (Corsi and Harvey, 1979;Kamp et al, 1979;Williams et al, 1979). The relatively unpopular response of picking another mode of transport (Response 6) was to some extent to be expected since for many destinations -particularly intercontinental destinations -air travel is generally considered to be the only viable alternative (Hares et al, 2010).…”
Section: Data Collectionsupporting
confidence: 82%
“…This response dimension is mentioned a few times in existing literature dealing with travel behaviour during the oil crises (e.g. Hunt 1974;Corsi and Harvey 1979). However, no studies were found in our literature assessment that investigated this response dimension more explicitly.…”
Section: Dimension 7: Postponement Of a Vacationmentioning
confidence: 83%
See 3 more Smart Citations